Burden of Proof in Environmental Disputes in the WTO: Legal Aspects - Henrik Horn; Petros C. Mavroidis (Research Institute of Industrial Economics (IFN), 2009)
This paper discusses allocation of burden of proof in environmental disputes in the WTO system. Besides laying down the natural principles that (i) the complainant carries the burden to (ii) make a prima facie case that its claim holds, WTO adjudicating bodies have said little of more general nature. The paper therefore examines the case law of relevance to environmental policies, to establish the rules concerning burden of proof that are likely to be applied in such disputes. Evaluating this case law, the paper makes two observations,: First, in cases submitted under the GATTWTO, adjudicating bodies have committed errors regarding the required amount of evidence (the burden of persuasion); and second, such errors, as well as errors concerning the determination of the party to carry the burden of providing this evidence (the burden of production), have been committed in disputes submitted under the TBT/SPS Agreements. These errors largely seem attributable to the general absence of methodology regarding the interpretation of some key substantive provisions featuring in the three Agreements.
Keywords: F13; Q56; 330; Burden of Proof; Burden of Production; Burden of Persuasion; WTO; Environment; WTO-Regeln; Rechtsprechung; Rechtsdurchsetzung; Umweltrecht; Umweltpolitik; Umweltschutz; Welt